A model proposal for the chaotic structure of Istanbul stock exchange - İşeri, Müge; Çağlar, Hikmet; Çağlar, Nazan (PERGAMON-ELSEVIER SCIENCE LTD, THE BOULEVARD, LANGFORD LANE, KIDLINGTON, OXFORD OX5 1GB, ENGLAND, 2008)
Chaos theory is considered a novel way of understanding the behaviour of nonlinear dynamic systems. It is well known that the evaluation of chaotic systems is dependent on initial conditions since exponential growth error is a common characteristic. This present paper evaluates the effects of a nonlinear dynamic system in Istanbul Stock Exchange, based on time series. The reliability of predicting stock behaviour depends on this fact. In other words, the aim is to prove that if ISE daily index return shows chaotic behaviour. (C) 2006 Elsevier Ltd. All rights reserved.
Keywords: time-series; dynamics; dimension; zaman serisi; dinamik; boyut